PENGARUH BUDAYA KERJA, INSENTIF TERHADAP KINERJA PETUGAS PEMUNGUT PAJAK MELALUI MOTIVASI KERJA BPPKAD KOTA PROBOLINGGO - Farid Hidayat; Mei Indrawati (Program Pascasarjana Universitas Wijaya Putra Surabaya, 2023)
This study aims to analyze whether work culture and incentives have a significant positive effect on the performance of local tax collection officers with work motivation as an intervening variable. The population of this study is a regional tax collection officer at the Probolinggo City Regional Financial and Asset Management Revenue Agency who has the status of a Civil Servant with a minimum service period of 1 year. The sample taken was 30 respondents. The analysis tool used is Smart PLS 3. The results showed that work culture has a direct positive effect on officer work motivation, work culture has a significant positive direct effect on officer performance, incentives have a significant positive direct effect on officer work motivation, incentives have a direct positive effect on officer performance, and work motivation has a direct positive effect on officer performance. Furthermore, work culture indirectly does not affect employee performance, incentives indirectly do not affect employee performance.